2020
DOI: 10.17309/jltm.2020.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Peculiarities of Motor Fitness of 8-Year-Old Schoolchildren

Abstract: The purpose of the study was to identify gender-related peculiarities of motor fitness of 8-year-old schoolchildren. Materials and methods. The study participants were 82 8-year-old schoolchildren (girls – 40, boys – 42). The children and their parents were informed about all the features of the study and gave their consent to participate in the experiment. The study used the following research methods: analysis of scientific and methodological literature, pedagogical observations, testing of motor fitness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…As in the studies by Ivashchenko, Nosko, Bartik, & Makanin (2020), Iermakov, Ivashchenko, & Khomiakov (2020), non-significant differences in the level of development of motor coordination and statistically significant differences in the level of development of strength, speed strength, speed, endurance, and in the level of proficiency in gymnastic exercises between girls and boys were observed, which indicates a need for dedicated development of motor skills. Such development is possible in teaching physical exercises with the use of programmed materials, as indicated by literature data (Shueva, Ivashchenko, & Jagiello, 2021;Suprun, Ivashchenko, & Cieślicka, 2021;Kharkovshchenko, 2022).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As in the studies by Ivashchenko, Nosko, Bartik, & Makanin (2020), Iermakov, Ivashchenko, & Khomiakov (2020), non-significant differences in the level of development of motor coordination and statistically significant differences in the level of development of strength, speed strength, speed, endurance, and in the level of proficiency in gymnastic exercises between girls and boys were observed, which indicates a need for dedicated development of motor skills. Such development is possible in teaching physical exercises with the use of programmed materials, as indicated by literature data (Shueva, Ivashchenko, & Jagiello, 2021;Suprun, Ivashchenko, & Cieślicka, 2021;Kharkovshchenko, 2022).…”
Section: Discussionmentioning
confidence: 51%
“…The problem of physical education of schoolchildren was given consideration with reference to their motor fitness (Ivashchenko, 2017), the effect of training loads on the dynamics of strength development , the effect of physical training modes on the effectiveness of motor skills formation Mugurdinova & Iermakov, 2022;Siedykh et al, 2022) and gender-related features of motor fitness (Iermakov et al, 2020;Khudolii, Golovnin et al, 2020;Petrov et al, 2020). It was found that the positive effect of learning depends on the level of motor skills development, consistent solving of learning tasks, and rational application of methods (Khudolii, 2019;Ivashchenko, 2020;Kharkovshchenko, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Формування рухових навичок у процесі фізичного виховання в школі займає чільне місце (Petrov, Khudolii, & Cieślicka, 2020;Shevchenko, Khudolii, & Potop, 2020;Iermakov, Ivashchenko, & Khomiakov, 2020). Так на основі факторного аналізу встановлено, що рівень навченості вправам визначає варіацію результатів тестування, а формування рухових навичок має пріорітет в освітньому процесі у молодшій школі.…”
Section: вступunclassified
“…• роль концентрації уваги у процесі формування рухових навичок (Bahmani, Babak, Land, Howard, Diekfuss, & Abdollahipour, 2021;Van Der Fels, Smith, De Bruijn, Bosker, Königs, Oosterlaan, Visscher, & Hartman, 2019); • критерії оцінки сформованості рухових навичок (Basman, 2019;Clark, Bisi, Duncan, & Stagni, 2021;Field, Crane, Naylor, & Temple, 2020); • гендерні особливості формування рухових навичок (Behan, Belton, Peers, O'Connor, & Issartel, 2019;Iermakov, Ivashchenko, & Khomiakov, 2020); • особливості формування рухових навичок у дітей молодшого шкільного віку (Jaikaew & Satiansukpong, 2021;Maurer & Roebers, 2019;Sigmundsson, Newell, Polman, & Haga, 2021); • режими виконання фізичних вправ у процесі формування рухових навичок (Iermakov, Ivashchenko, Khudolii, Chernenko, Veremeenko, & Zelenskyi, 2021;Marchenko & Kovalenko, 2020). Ефективними методами аналізу результатів навчання є баготовимірні статистики (Khudolii, Ivashchenko, & Beketov, 2015;Ivashchenko, Iermakov, Khudolii, Cretu, & Potop, 2017;.…”
Section: вступunclassified
See 1 more Smart Citation